2011
DOI: 10.1016/j.bbi.2010.12.014
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 signaling mediates morphine-induced tactile hyperalgesia

Abstract: Morphine and related compounds are the first line of therapy in the treatment of moderate to severe pain. Over time, individuals taking opioids can develop an increasing sensitivity to noxious stimuli, even evolving into a painful response to previously non-noxious stimuli (opioid-induced hyperalgesia; OIH). The mechanism underlying OIH is not well understood although complex intracellular neural mechanisms, including opioid receptor desensitization and down-regulation, are believed to be major mechanisms unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 56 publications
(67 reference statements)
4
70
0
2
Order By: Relevance
“…Recently, evidence from an in vivo study directly proves that CXCL12/CXCR4 axis was essential to the pathology of OIH (Wilson et al, 2011). In this study, it was found that repeated intraperitoneal injection of morphine induced tactile hyperalgesia, which was attenuated by intraperitoneal administration of AMD3100 in rats.…”
Section: Cxcl12/cxcr4 Axis and Oihmentioning
confidence: 61%
See 2 more Smart Citations
“…Recently, evidence from an in vivo study directly proves that CXCL12/CXCR4 axis was essential to the pathology of OIH (Wilson et al, 2011). In this study, it was found that repeated intraperitoneal injection of morphine induced tactile hyperalgesia, which was attenuated by intraperitoneal administration of AMD3100 in rats.…”
Section: Cxcl12/cxcr4 Axis and Oihmentioning
confidence: 61%
“…Even though some reasons for the poor response have been proposed, like pharmacokinetic properties, species selectivity, and drug metabolism (Gao and Ji, 2010), an effective solution to this problem has not been reported. In our previous study, it was found that the antiallodynia effects of AMD3100 by injecting centrally lasted for 3-4 days (Luo et al, 2014), but such effects by injecting peripherally only lasted for hours (Bhangoo et al, 2007b(Bhangoo et al, , 2009Dubovy et al, 2010;Wilson et al, 2011). Therefore, we hypothesize that the efficacy of CXCL12/CXCR4 axis-related therapy may depend on how it is delivered, and more evidence is needed to prove this.…”
Section: Prospectmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that CXCL12 and CXCR4 actively participate in nociception via direct stimulation of nociceptive neurons (23), via induction of mechanical hypersensitivity in rats (24), or via desensitization of opioid receptors, but all these effects are in the central nervous system (25). In the present study, we show this chemokine-receptor axis has a role in the activation of peripheral glia, i.e., SC, in the tumor microenvironment, which seems to entail an analgesic effect in the early disease course.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of CXCL12 to CXCR4 activates multiple signaling pathways, including the extracellular signal-regulated kinase (ERK), phosphatidylinositol 3-kinase-Akt, cAMP/ cAMP-dependent protein kinase, and phospholipase C pathways, and results in increased intracellular calcium levels and the release of cytokines by glial cells [8][9][10]. Increasing evidence suggests that CXCL12/CXCR4 play important roles in nociceptive signal processing [11][12][13][14]. They are widely distributed and constitutively expressed in small amounts in small-and medium-sized dorsal root ganglia (DRG) neurons and glia (satellite cells) and in the spinal cord [15,16].…”
Section: Introductionmentioning
confidence: 99%